CHINESE WHISPER GAME AS ONE ALTERNATIVE TECHNIQUE TO TEACH SPEAKING - Utami, Putri; Rahmawati, Istiqomah Nur (English Education: Jurnal Tadris Bahasa Inggris, 2018)
When doing teaching, the teacher sometime uses games in delivering the material in order to make it fun. Wright et al said that games also help the teacher to create contexts in which the language is useful and meaningful. Whisper game, also known as ‘the broken telephone’, is a game that whisper or pass the message from person to person in a group, and the last person will announce the message that he/she got and compare it with the first person to see the similarity. The interested one of these games is sometimes the message will change to another message or information. In this research the writers used experimental method by using quasi experimental pre-test-post-test group design. The pre-test was given before the treatment at the eighth grade of one Junior High School in South Lampung. At the end of the treatment, the writers gave the students a test, which was called post-test. Towards the end, the score of pre-test and post-test compared in order to find the answer for the research questions. After giving the post-test, then the writers analyzed the data. From the data analysis, it was found that the result of independent sample T-test was 2.99. This result then was consulted to the score of T-critical, in this case T-critical 0.05 was 2. The hypothesis proposal was that Ho is accepted, if the score of Tobserve>Tcritical. From analysis the score of T-observe was higher than T-critical (0.05), so Ho was accepted, in other words, from this research, it was known that Chinese Whisper Game could improve the students’ speaking ability. Therefore, there was a significant influence of using Chinese Whisper Game towards students’ speaking ability.Key words: Chinese Whisper Game, Experimental Design, Speaking Ability